Quality Control of Janggelan Products Using Statistical Quality Control (SQC) and Failure Mode Effect Analysis (FMEA) Methods in UD. Rizqi Agung - Faizal, M. Rizki Nur; Rochmoeljati, Rr. (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
UD. Rizqi Agung is one of the SMEs in Ngrayun, Ponorogo. This SMEs is one of the medium-sized SMEs that produces packaged drinks. The packaged drinks produced are drinks made from janggelan juice. UD. Rizqi Agung has a production process that is still semi-manual so that there are still products that still have defects in these products. The methods used are Statistical Quality Control (SQC) and Failure Mode and Effect Analysis (FMEA). SQC tools are check sheet, stratification, histogram, paretto diagram, scatter diagram, control chart, and cause and effect diagram. While FMEA is used for improvement of the results of the cause and effect diagram. Based on the results of research on Sari Janggelan products, the most dominant defect is obtained, namely Cup Dent defects (4.06%), followed by Leak defects (2.84%), Dented Cardboard defects (1.30%), and Label not Symetric defects (1.22%). Proposed improvements with FMEA obtained risks that have the highest priority level to make improvements to minimize the possibility of errors. The highest RPN values is 320 and 288 of the type of cup dent defect with proposed improvement recommendations, namely changing cup vendors to match the quality requested by SMEs and monitoring employee performance.